Disturbing hypotheses in tropical forests - Sheil, Douglas; Burslem, David F.R.P. (2003)
The intermediate disturbance hypothesis (IDH) is a controversial explanation for the maintenance of tropical forest tree diversity, but empirical tests of it are rare. Two data intensive evaluations have recently yielded contradictory outcomes: one for and one against the IDH. This article proposes that the explanation for these results lies in the subtleties of divergent interpretations and approaches, and in the different characteristics of the study sites. The apparent simplicity of the IDH is deceptive, because a range of distinct phenomena is involved, each of which can be defined and examined. Recent developments offer exciting opportunities for a deeper comprehension of how disturbance influences forest diversity.